Coleoptera Lamellicornia fauna of the sugar cane area of the sugar plantation of Atencingo, Puebla, Mexico - Aragón-García, Agustín; Morón Ríos, Miguel Ángel; Damián-Huato, Miguel Ángel; López-Olguin, Jesús Francisco; Pinson-Rincón, Erika Patricia; Peréz-Quintanilla, José Nelson (Instituto de Ecología, A.C., 2012)
With the purpose of evaluating the abundance of beetles (Scarabaeoidea) of the sugar cane area of Atencingo southward of the state of Puebla, captures were carried out during the period of2000 to 2003 by using a screen-type light trap provided with a 120 watts mercury vapor light lamp, as well as direct collection under the public illumination and on tree and bush foliage. A total of 1253 specimens representing four families, six subfamilies, 11 tribes and 23 species of the genera Cotinis, Cyclocephala, Digitonthophagus, Diplotaxis, Epectinaspis, Ligyrus, Paranomala, Phileurus, Phyllophaga, Polyphylla, Ptichopus and Strategus were collected. Best represented genus was Phyllophaga with five species. Most abundant species were Cyclocephala lunulata and Phyllophaga brevidens, each with 534 and 539 specimens, respectively. A key to the 23 species is included.